Measured and Perceived Conditions of Indoor Environmental Qualities (IEQ) of University Learning Environments in Semi-arid Tropics: a Field Study in Kano-Nigeria - Ali, Sani Muhammad (University of Portsmouth, 2018)
This study investigates the conditions and the levels of satisfaction with indoor environmental quality (IEQ) in naturally ventilated (NV) learning environments in Bayero University, Kano and compares the results to international comfort standards’ thresholds. It examines the thermal and visual comfort, acoustic quality as well as the indoor air quality of six learning environments in the University consisting of four lecture theatres and two laboratories. Researches in IEQ have shown that good quality indoor environment enhances occupants’ comfort, wellbeing, raises their productivity, and most importantly for this research, it raises students’ performances, reduces absenteeism, and reduces stress and fatigue among teachers. IEQ researches are mostly being undertaken in the four most advanced continents that are situated in the temperate regions of the world, but not in subSaharan Africa. Using both measurement and survey methods, internal and external physical parameters (air and radiant temperatures, air velocity, relative humidity, background noise, sound pressure level, horizontal and vertical illumination level, carbon dioxide concentration and particulate matter) were evaluated. The assessments were undertaken three times covering ten months, August 2016 to May 2017, which coincided with the three distinct seasons (warm and wet; cool and dry & hot and dry) in Kano. PMV model, as always, failed to predict the thermal conditions of the learning environments. Similarly some of the measured and calculated IEQ parameters, have not met the thresholds specified by the adaptive components of ASHRAE-55, but were in agreement with EN 15251, the respondents expressed their acceptance of their learning environments, subjectively. This is not surprising as these standards were often based on experiments implemented in developed countries, where the severity of the climatic conditions and the culture are dissimilar to sub Saharan Africa. The outcome of the research is hoped to raise awareness of IEQ potentialities among the academia, building industry professionals, building owners, university managers and other education policy makers in the region.
KerkoCite.ItemAlsoKnownAs: 2129771:26HE8V5M 2129771:26HE8V5M 5072953:LPAYJVWN 5072953:PKE3SFJF
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; evidence_review_2; openalex:n:0; ⛔ No DOI found

A review on windcatcher for passive cooling and natural ventilation in buildings, Part 1: Indoor air quality and thermal comfort assessment - Jomehzadeh, Fatemeh; Nejat, Payam; Calautit, John Kaiser; Yusof, Mohd Badruddin Mohd; Zaki, Sheikh Ahmad; Hughes, Ben Richard; Yazid, Muhammad Noor Afiq Witri Muhammad (Renewable and Sustainable Energy Reviews, 2017)
The most prominent challenge in 21th century is global warming which seriously threats the mankind. Building sector with 40% of global energy consumption and GHG emission play a key role in this threat. In this regard, the impact of cooling systems cannot be ignored where along with ventilation and heating systems totally account for 60% of energy consumed in buildings. Passive cooling systems can be a promising alternative to reduce energy consumption. One of the oldest passive cooling system that is still being used today is windcatcher. By manipulating pressure differences and the buoyancy effect, an adequate level of ventilation in buildings can be provided by windcatchers. Since most of the previous windcatcher studies assessed the design characteristics, the current investigation focused on the indoor air quality (IAQ) and thermal comfort aspects. The review details and compares the different theoretical and experimental methods employed by researchers in different case studies to assess the IAQ and thermal comfort. It was found that most IAQ studies were conducted in the UK using CFD and experimental techniques. Previous studies assessed IAQ based on several parameters such as air flow rate, air change rate, CO2 concentration, air change effectiveness and mean age of air. The findings of the studies revealed that satisfactory IAQ were generally achieved using the windcatcher. On the other hand, thermal comfort studies of windcatchers were mainly conducted in hot climates such as in the Middle East. In addition to night ventilation, the review also looked into the different types of cooling methods incorporated with windcatchers such as evaporative cooling, earth to air heat exchangers (EAHE) and heat transfer devices (HTD). Night ventilation was found to be effective in temperate and cold conditions while additional cooling using evaporative cooling, EAHE and HTD were found to be necessary in hot climates.
openalex: W2560795218 KerkoCite.ItemAlsoKnownAs: 10.1016/j.rser.2016.11.254 4874017:9W6ID58Z 5072953:8LUI5SFF 5072953:WV2R5MRE
Keywords: _z:class:countries; _z:class:themes; oa:keyword:indoor air quality; oa:keyword:natural ventilation; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; oa:topic:T13298 Solar Chimney Systems; openalex:n:1; openalex:yes